Molecular analysis of T-DNA insertion mutants identified putative regulatory elements in the AtTERT gene - Fojtová, Miloslava; Peška, Vratislav; Dobšáková, Zuzana; Mozgová, Iva; Fajkus, Jiří; Sýkorová, Eva (Journal of experimental botany, 2011)
Analysis of plants bearing a T-DNA insertion is a potent tool of modern molecular biology, providing valuable information about the function and involvement of genes in metabolic pathways. A collection of 12 Arabidopsis thaliana lines with T-DNA insertions in the gene coding for the catalytic subunit of telomerase (AtTERT) and in adjacent regions was screened for telomerase activity [telomere repeat amplification protocol (TRAP) assay], telomere length (terminal restriction fragments), and AtTERT transcription (quantitative reverse transcription-PCR). Lines with the insertion located upstream of the start codon displayed unchanged telomere stability and telomerase activity, defining a putative minimal AtTERT promoter and the presence of a regulatory element linked to increased transcription in the line SALK_048471. Lines bearing a T-DNA insertion inside the protein-coding region showed telomere shortening and lack of telomerase activity. Transcription in most of these lines was unchanged upstream of the T-DNA insertion, while it was notably decreased downstream. The expression profile varied markedly in mutant lines harbouring insertions at the 5' end of AtTERT which showed increased transcription and abolished tissue specificity. Moreover, the line FLAG_385G01 (T-DNA insertion inside intron 1) revealed the presence of a highly abundant downstream transcript with normal splicing but without active telomerase. The role of regulatory elements found along the AtTERT gene is discussed in respect to natural telomerase expression and putative intron-mediated enhancement.
Keywords: proteiny huseníčku; inzerční mutageneze; DNA, Bacterial; Arabidopsis; Mutagenesis, Insertional; telomerasa; Genotype; Reverse Transcriptase Polymerase Chain Reaction; genotyp; regulační oblasti nukleových kyselin; Arabidopsis Proteins; Telomerase; Regulatory Sequences, Nucleic Acid; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; polymerázová řetězová reakce s reverzní transkripcí; DNA bakterií